2022
DOI: 10.17079/jkgn.2022.24.3.291
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Moral Distress, Empowerment and Nursing Practice Environment on Nurses’ Person-centered Care in Long-term Care Hospitals: A Cross-Sectional Study

Abstract: Purpose: The purpose of this study was to identify the influence of moral distress, empowerment, and nursing practice environment on nurses’ person-centered care in long-term care hospitals.Methods: A cross-sectional descriptive study was conducted using self-report questionnaires. Participants included 128 nurses working in eight long-term care hospitals. Data were collected from July 24 to August 31, 2018 and analyzed using the independent t-test, one-way ANOVA, Pearson correlation, and multiple linear regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
1
0
3
Order By: Relevance
“…It was also consistent with the lowest autonomy score in healthcare facility nurses in another study [28]. This result means that long-term care hospital nurses do not guarantee free decision-making rights to older adults because they provide uniform and mechanical care [13]. Therefore, it is necessary to prepare measures to support older adults in long-term care hospitals to participate in treatment and care with autonomous decision-making rights.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It was also consistent with the lowest autonomy score in healthcare facility nurses in another study [28]. This result means that long-term care hospital nurses do not guarantee free decision-making rights to older adults because they provide uniform and mechanical care [13]. Therefore, it is necessary to prepare measures to support older adults in long-term care hospitals to participate in treatment and care with autonomous decision-making rights.…”
Section: Discussionsupporting
confidence: 64%
“…Previous research has reported factors that influence the person-centered care practice, such as care competence [11], self-leadership [12], and empowerment [13]. These factors are similar to professional competence and interpersonal skills among the qualities of care providers as identified by McCormack and McCance [9] in their framework for the person-centered care practice, and care competence can be said to be an encompassing concept.…”
Section: Based On This Mccormack and Mccancementioning
confidence: 96%
“…이외 간호사들이 임 상에서 경험하는 도덕적 고뇌 [7], 정신과 병동 간 호사의 도덕적 고뇌, 전문직 자아개념 및 직무만 족도 [8], 병원간호사의 도덕적 고뇌, 신체증상 및 소진의 관계 [9], 중환자실 간호사가 경험하는 말 기환자간호의 어려움과 도덕적 고뇌, 소진 및 직 무만족과의 관계 [10] 등이 있었다. 또한 요양병 원 간호사의 도덕적 고뇌와 도덕적 민감성 [11], 요양병원 간호사의 도덕적 고뇌, 임파워먼트, 간 호근무환경이 인간중심돌봄에 미치는 영향 [12] 등 요양병원 간호사를 대상으로 한 연구가 활발 해지고 있었다. 해외에서는 Corley [2]가 도덕적 고뇌와 윤리적 딜레마를 구별하는 것이 매우 중요하며, 임상에 서 피할 수 없고 늘 경험하게 되는 도덕적 고뇌를 장점으로 활용할 수 있도록 간호학생 때부터 윤 리 지식 위주의 교육이 아닌 임상 현장에 직면하 는 다양한 도덕적 고뇌 상황에 직면하도록 교육 할 것을 주장하였다.…”
Section: 서론unclassified
“…간호 근무환경은 간호사 가 환자에게 전문적인 간호를 제공할 수 있도록 지원하는 물리적, 인 적 환경을 포함한 조직의 특성을 의미한다 [15]. 일부 요양병원 간호사 들은 기관의 교육, 간호인력, 재정적 지원 부족과 전문 인력 부족으로 인한 과중한 업무, 업무능력의 한계, 비체계적인 간호 지원인력 관리 등의 부담감으로 간호 수행에 어려움을 겪고 있다 [16,17] (1) 대상자의 일반적 특성을 파악한다.…”
unclassified
“…Jung and Min[16]의 연구 결과와 일치하였다 그리고, 치매 태도와 인 간중심 돌봄의 관계는 선행연구에서 다양한 결과를 보였는데, 본 연구 의 결과와 비슷한 결과를 보인 Lin et al[26]의 연구는 국내 간호대학 에서는 치매 노인을 간호하는 내용에서 현실 중심 접근인 사람, 시간, 장소 등을 인지하도록 하는 교육을 시행하고 있어 인간중심 접근법과 는 거리가 먼 교육을 시행하고 있기 때문이라고 하였으며 본 연구의 결 과에 지지되는 논리이다. 그러나 위의 결과는 Lee and Jung [19]의 연구 와는 차이가 있는 결과로, Lee and Jung [19]의 연구에서는 인간중심 돌봄은 치매 태도와 양의 상관관계를 보였다.…”
unclassified